Civil liability of a franchise network organizer for violations of labor rights against employees employed by a network participant based on atypical forms of employment - Mielnik-Kurek, Monika (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
In the presented text, the author analyzes the possibility of attributing to the organizer of a franchise network liability for violations of labor rights against employees employed by a network participant based on atypical forms of employment. In principle, the franchise network is independent network participants as separate legal entities, thus they should be treated as independent employers. Nevertheless, this balance can be disturbed by the network organizer, which, within the framework of its contractual powers, can exercise control over the implementation of the franchise package, which consequently manifests itself as sovereign interference in the independent decisions of employer- participants of the network. This is important in the perspective of the increasingly popular atypical forms of employment, under which the application of flexible employment policies to the strategic resources of the company can lead not only to the “flight” of professionals of the organization to other employers, but also to other risks associated with the undertaking of competitive activities against the employer by people who, while occupying an important position in the network participant, are employed on a discretionary basis and do not identify with the implementation of its objectives. The purpose of this article is to analyze the admissibility of attributing to the organizer of the network the characteristics of an employer, as well as the possibility of attributing to it liability for damage caused to employees.